THE CONSTRUCTION OF INDIE MUSIC FANDOM IDENTITY ON INSTAGRAM - Narendra Wigati, Oki Turatula; Mulyadi, Raden Muhammad; Nugrahanto, Widyo (Capture : Jurnal Seni Media Rekam, 2022)
This article discusses the significance of indie music fandom, particularly their involvement in collecting physical music releases, namely vinyl records, cassettes, and CDs uploaded to Instagram social media. This study aims to examine how the identity of indie music fandom is formed on social media and the motivations for uploading a collection of physical music releases. This research is a qualitative netnographic study supported by observing the content of fandom accounts, conducting interviews, and employing Content Analysis techniques. The results of this study indicate that past experiences, personality, and pride motivate indie music fandom to construct an identity through the collection and uploading of physical music releases on Instagram.